2004
DOI: 10.1002/glia.20076
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐dependent potassium currents in hypertrophied rat astrocytes after a cortical stab wound

Abstract: Changes in the membrane properties of reactive astrocytes in gliotic cortex induced by a stab wound were studied in brain slices of 21-28-day-old rats, using the patch-clamp technique and were correlated with changes in resting extracellular K+ concentration ([K+]e) measured in vivo using K+-selective microelectrodes. Based on K+ current expression, three types of astrocytes were identified in gliotic cortex: A1 astrocytes expressing a time- and voltage-independent K+ current component and additional inwardly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 58 publications
9
35
0
Order By: Relevance
“…There is a possibility that these currents are masked by the conductance of the syncytium, but neither leak subtraction, nor blockade of gap junction coupling, provided proofs of any voltage-gated currents in passive astrocytes. The high number of passive cells is in line with a recent study from the nucleus accumbens (D'Ascenzo et al, 2007), while studies from other brain regions have shown a larger population of complex astrocytes (Anderova et al, 2004;Bordey and Sontheimer, 1998;Isokawa and McKhann, 2005). The difference in proportion is likely dependent on the brain region analyzed and may be connected to the prevalence of gap junction coupling (Sontheimer et al, 1991).…”
Section: Discussion Passive Astrocytes Outnumber Complex Cells In Thesupporting
confidence: 80%
See 1 more Smart Citation
“…There is a possibility that these currents are masked by the conductance of the syncytium, but neither leak subtraction, nor blockade of gap junction coupling, provided proofs of any voltage-gated currents in passive astrocytes. The high number of passive cells is in line with a recent study from the nucleus accumbens (D'Ascenzo et al, 2007), while studies from other brain regions have shown a larger population of complex astrocytes (Anderova et al, 2004;Bordey and Sontheimer, 1998;Isokawa and McKhann, 2005). The difference in proportion is likely dependent on the brain region analyzed and may be connected to the prevalence of gap junction coupling (Sontheimer et al, 1991).…”
Section: Discussion Passive Astrocytes Outnumber Complex Cells In Thesupporting
confidence: 80%
“…The majority of cells (95%) were passive astrocytes that exhibited relatively linear current/voltage relationships. Three different membrane current patterns could be distinguished in this group of cells, and are referred to as A1, A2 and A3 astrocytes (Fig 1) (Compare to (Anderova et al, 2004)). Cells with an A1 current pattern (56%) exhibited a large voltage independent conductance and a slowly decaying current component.…”
Section: Membrane Current Pattern and Electrophysiological Propertiesmentioning
confidence: 95%
“…Because our previous molecular and physiological data in mouse and rat models of albumin-and TGF-b-induced seizures showed early activation of astrocytes (3,10), and specifically a robust excessive extracellular potassium accumulation upon repetitive stimulation at physiologically relevant frequencies (10-50 Hz) (10), we tested a potential role of such stimulation on neuronal excitability in the IL-6-treated cortices. Our recordings demonstrate a long-lasting depolarization (∼8 mV) upon afferent but not intracellular stimulation, predicting a 25% increase in the accumulation of extracellular potassium during neuronal activation, consistent with the notion of astrocytic dysfunction and reduced potassium buffering after insult (51,52) or during epileptogenesis (3,10). Overall, although additional experiments in different neuronal populations and experimental conditions (e.g., voltage clamp experiments under different holding membrane potentials) are required to rule out additional changes in synaptic properties, our experiments at an early time point during epileptogenesis suggest that IL-6 is sufficient to facilitate stimulus-dependent neuronal depolarization and hyperexcitability, likely due to failure in buffering of extracellular potassium.…”
Section: Discussionsupporting
confidence: 85%
“…Several previous studies have shown that reactive astrocytes express voltage-gated currents (Hinterkeuser et al, 2000;MacFarlane and Sontheimer, 1997) which are affected by proliferation at the site of injury (Bordey et al, 2000(Bordey et al, , 2001). An upregulation of K dr currents in reactive astrocytes was reported in situ (Bordey and Sontheimer, 1998;Bordey et al, 2001) and in vitro (Anderova et al, 2004;MacFarlane and Sontheimer, 1997;Perillan et al, 1999Perillan et al, , 2000. These outwardly rectifying K 1 chan-nels are thought to be involved in the control of cell proliferation.…”
Section: Introductionmentioning
confidence: 93%